A linguagem em Quine - Oliveira, Sandra Maria de (2011)
The scope of the discussion about language is very broad. Thus, we have searched to provide elements that underlie the problem of this thesis, whose core focuses on developments concerning the approaches of behaviorism, empiricism and pragmatism, as well as key concepts in the quinean system in order to clarify his thought to support this research. In this context, the problem of this study is to search basis in Quine's theory of language to answer the question in relation to behavioral bias raised, namely, which philosophical idea permeates Quine s philosophical theory of language. This investigation has been guided from basic quinean texts, such as: From a Logical Point of View; Word and Object; Ontological Relativity and Other Essays; Pursuit of Truth; The Ways of Paradox and Other Essays; The Web of Belief; The Roots of Reference; Theories and Things. Regarding to Dewey, the study has grounded in the book Experience and Nature, in which he, incisively, show his concepts about language. Moreover, from the texts, it can be possible to answer the hypotheses and questions that have motivated this research, concerning language and its assumptions on Quine. Furthermore, we have presented relevant concepts to the issue of uncertainty and assumptions that have been discussed in Chapter 2. In the third, language and empiricism can show the world of experience that there is on Quine's philosophical system. Finally, in the final remarks, we conclude that, indeed, Quine's theory about language, learning and acquisition has a strong behaviorist nature, confirming the initial hypothesis.